Memberdayakan Olah Raga Nasional - Hadjarati, Hartono (Jurnal Pelangi Ilmu, 2009)
Athletics done correctly and correctness will become a real important factor supports for expansion of potency early. Health, corporeal fitness and pre-eminent personality characters is a real factor supports for expansion of man xśelf potency, and through physical education, recreation, and correct sport of the obtainable factors. Pass construction of systematic athletics, quality of Human Resources Development can be aimed at improvement of selfcontrol, responsibility, discipline, and high sportivity